Instagramable and Memorable Travel Experiences and Their Influence on Revisit Intentions at the Bagendit Tourism Site Post-Revitalization - Adiatma, Dani; Rukma, Deden Firman Syuyaman; Rahayu, Diana (Jurnal Wacana Ekonomi, 2024)
This research aims to find out the picture related to instagrammable, memorable tourism experience and revisit intention, as well as examining the impact of instagramable and memorable tourism experience on revisit intention at Situ Bagendit after revitalization using descriptive and verification quantitative methods. The data collection technique was carried out through distributing questionnaires and then the data was analyzed using the structural equation model partial least squares (SEM-PLS) with statistical tools in the form of SMART-PLS version 3. This research resulted in an overall picture related to instagrammability, memorable tourism experience and revisit intention. in Situ Bagendit after revitalization it is in the good category. Apart from that, it was found that there was a positive and significant influence of instagrammable and MTE on the intention to revisit Situ Bagendit after revitalization.